High resolution genomic profiling and classical cytogenetics in a group of benign and atypical meningiomas - Holland, Heidrun; Mocker, Kristin; Ahnert, Peter; Kirsten, Holger; Hantmann, Helene; Koschny, Ronald; Bauer, Manfred; Schober, Ralf; Scholz, Markus; Meixensberger, Jürgen; Krupp, Wolfgang (Cancer genetics, 2011)
Meningiomas are classified as benign, atypical, or anaplastic. The majority are sporadic, solitary, and benign tumors with favorable prognoses. However, the prognosis for patients with anaplastic meningiomas remains less favorable. High resolution genomic profiling has the capacity to provide more detailed information. Therefore, we analyzed genomic aberrations of benign and atypical meningiomas using single nucleotide polymorphism (SNP) array, combined with G-banding by trypsin using Giemsa stain (GTG banding), spectral karyotyping, and locus-specific fluorescence in situ hybridization (FISH). We confirmed frequently detected chromosomal aberrations in meningiomas and identified novel genetic events. Applying SNP array, we identified constitutional de novo loss or gain within chromosome 22 in three patients, possibly representing inherited causal events for meningioma formation. We show evidence for somatic segmental uniparental disomy in regions 4p16.1, 7q31.2, 8p23.2, and 9p22.1 not previously described for primary meningioma. GTG-banding and spectral karyotyping detected a novel balanced reciprocal translocation t(4;10)(q12;q26) in one benign meningioma. A paracentric inversion within 1p36, previously described as novel, was detected as a recurrent chromosomal aberration in benign and atypical meningiomas. Analyses of tumors and matched normal tissues with a combination of SNP arrays and complementary techniques will help to further elucidate potentially causal genetic events for tumorigenesis of meningioma.